Pengaruh Tawakal Terhadap Stres Akademik pada Mahasiswa - Mutiara Wulandari; Basti Tetteng; Ahmad Yasser Mansyur (Universitas Negeri Makassar, 2023)
Surrender to God (Tawakal) potentially can be a source of strength for students in decreasing academic stress while completing academic assignments. This study aims to determine the impact of tawakal (X) on academic stress (Y) with a quantitative model with simple random sampling to collect participants from a total of 302 (100 males, 202 females). The data instruments using two modified scales namely Tawakal and academic stress scale in Likert-form respectively, Using Simple Regression Test after normality and linearity are fulfilled, showed that there was a negative impact of tawakal on academic stress (r = -0,152, p < 0.05) by the increase in tawakkal score decreases the academic stress, and vice versa along with effect-size 2.31%. The study is expected to be additional information related to tawakal variables as well as measurement construct, its impact on maintaining psychological health, and implied as an intervention model to reduce academic stress.